The emerging policy for green economy and social development in Limpopo, South Africa - Agnes Musyoki (United Nations Research Institute for Social Development (UNRISD), 2012)
Many countries in Africa are already experiencing negative impacts of climate change,prompting the emergence of various policies to mitigate and adapt to these changes. This paper evaluates the emerging green economy in South Africa, using ideas from the concept of sustainable rural livelihoods. Rural livelihoods in Africa and other developing countries are intimately connected to ecological services. Contrary to the dominant development discourse where African societies are reflected as being helpless, communities and governments are prioritizing green economy for job creation, poverty alleviation and reducing inequalities, while addressing global environmental concerns. But the concepts of sustainable development and green economy have both been criticized for lack of clear definitions. While it is agreed that there is a lack of clarity on the two concepts and failure in implementation at the global level, this paper argues that the key tenets of the two concepts are particularly relevant for rural development. What remains problematic, however, is how objectives of a green economy and sustainable development are to be achieved. One of the key challenges in South Africa, and other developing countries, is the gap between policy and implementation of sustainable development, the Millennium Development Goals and other such globally driven initiatives. A central question is, therefore: what needs to be done in order for local economies and societies to realize mutual objectives of investing in natural capital, decarbonizing the economy and creating green jobs? Of major concern in this paper is how green economy policies and proposals can stimulate growth and development in rural areas and improve rural livelihoods...
Keywords: 330